Demokrasi Semu di Singapura Pada Masa Pemerintahan Lee Kuan Yew (1959 - 1990) - Antriksa, Febbie Ardilla (Program Studi Hubungan Internasional FISIP Universitas Udayana, 2014)
ABSTRACT The purpose of this research is to look at the democratic system that occurred in Singapore during Lee Kuan Yew era. Singapore as a small but well developed country in Southeast Asia is well-known with its parliamentary democratic system. But, during Lee Kuan Yew era, the implementation of democratic system is not a pure democratic as espoused by west. Singapore has a multi-party system but dominated by People’s Action Party (PAP) that Lee Kuan Yew established. Through the hybrid regime that affected by Asian Values and the implementation of Internal Security Act, Lee Kuan Yew, with his party developed his own version of democracy. Keywords: democrary, Singapore, Lee Kuan Yew, hybrid regime